Mechanical strength enhancement of porous nanocrystalline-silicon (pnc-Si) membrane via titanium-oxide (Ti-O) coating - Rhonira Latif,; Muhammad Fahmi Jaafar,; Mohd Faizal Aziz,; Burhanuddin Yeop Majlis, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Porous nanocrystalline silicon (pnc-Si) membrane is mainly studied as a blood filtration membrane, mimicking the glomerulus filtration membrane of a human kidney. However, the pnc-Si material itself is not hemocompatible and enormous membrane area to thickness ratio makes the membrane to be easily fractured. Silicon surface modification via titanium-oxide (Ti-O) thin film layer deposition has been proven to be hemocompatible and the presence of Ti-O layer has been numerically studied to give higher membrane flexural strength. In this work, square pnc-Si membranes of 2 mm × 2 mm × 20 nm size have been fabricated with and without Ti-O layer. Point loading-unloading nanoindentation method has been performed and the membranes’ displacement behaviour subjected to point loads is studied. The pnc-Si membranes with Ti-O layer were found to attain higher fracture strength, membrane bending stiffness and average hardness with the increase of ~20, ~11 and ~24%, respectively, compared to bare pnc-Si membranes. The mechanical strength of a free-standing pnc-Si membrane is improved by depositing a Ti-O thin film layer on the membrane structure.